2019
DOI: 10.1038/s42003-019-0282-0
|View full text |Cite
|
Sign up to set email alerts
|

A high-throughput microscopy method for single-cell analysis of event-time correlations in nanoparticle-induced cell death

Abstract: The temporal context of cell death decisions remains generally hidden in ensemble measurements with endpoint readouts. Here, we describe a method to extract event times from fluorescence time traces of cell death-related markers in automated live-cell imaging on single-cell arrays (LISCA) using epithelial A549 lung and Huh7 liver cancer cells as a model system. In pairwise marker combinations, we assess the chronological sequence and delay times of the events lysosomal membrane permeabilization, mitochondrial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…We believe that fluorescence of the Cy5 labeled mRNAs is unquenched during the time of uptake due to unpacking of the lipid-based carriers. Other studies also used multiple fluorescent signals in single cell time lapse measurement to exploit signal correlations (36,37). Our findings are in agreement with a study by Yasar et al showing that the kinetics of mRNA nanocarrier binding on the cell surface is the same for transfected and nontransfected cells without giving further insights on transfection efficiency (26).…”
Section: Discussionsupporting
confidence: 91%
“…We believe that fluorescence of the Cy5 labeled mRNAs is unquenched during the time of uptake due to unpacking of the lipid-based carriers. Other studies also used multiple fluorescent signals in single cell time lapse measurement to exploit signal correlations (36,37). Our findings are in agreement with a study by Yasar et al showing that the kinetics of mRNA nanocarrier binding on the cell surface is the same for transfected and nontransfected cells without giving further insights on transfection efficiency (26).…”
Section: Discussionsupporting
confidence: 91%
“…Bulk-based studies fail to address the functional heterogeneity underlying a given cell population by masking the phenotype, gene expression, and the mechanism of cellular communication in between individual immune cells 11 , 12 . To overcome the limitations of bulk methodologies, the study of cytotoxicity at a single-cell level can be performed using flow cytometry-based assays and single cell microscopy assays 13 , 14 . However, flow cytometric assays are snapshot-based and therefore not suited to monitor temporal dynamics of cellular interactions leading to cytotoxicity 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Additional studies suggested that cytosolic K + depletion by nigericin alone is a minimal common cellular event that is sufficient to activate the NLRP3 inflammasome [ 14 , 17 ]. Other studies have proposed a role for particle-induced lysosomal membrane permeability (LMP) in inflammasome activation and cell death [ 11 , 18 , 19 ]. However, the exact underlying mechanisms leading to LMP have not been described and determination of whether there is any relationship between LMP and changes in cytosolic [K + ] remain to be clarified.…”
Section: Introductionmentioning
confidence: 99%